2018
DOI: 10.3389/fimmu.2018.02997
|View full text |Cite
|
Sign up to set email alerts
|

Sex Bias in Asthma Prevalence and Pathogenesis

Abstract: Sex-related differences in asthma prevalence are well established and change through the reproductive phases of life. As children, boys have increased prevalence of asthma compared to girls. However, as adults, women have increased prevalence of asthma compared to men. Many factors, including genetics, environment, immunological responses, and sex hormones, affect the sex disparity associated with the development and control of asthma and other allergic diseases. Fluctuations of hormones during puberty, menstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
99
1
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(123 citation statements)
references
References 101 publications
8
99
1
8
Order By: Relevance
“…These observations have been frequently linked to the effect of female sex hormones in allergic asthma that have been well documented by us and other authors . In this regard, it has been shown that variations in female sex hormones during puberty, pregnancy or menopause can have a profound effect on asthma symptoms and severity …”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…These observations have been frequently linked to the effect of female sex hormones in allergic asthma that have been well documented by us and other authors . In this regard, it has been shown that variations in female sex hormones during puberty, pregnancy or menopause can have a profound effect on asthma symptoms and severity …”
Section: Discussionsupporting
confidence: 53%
“…Sex differences in asthma have been well described in the literature. Several reports have shown that asthma is more prevalent in boys than in girls but this status is inverted during puberty, indicating an important role for sex hormones in the development of this disease . Similarly, the influence of obesity has also been documented with studies indicating that body weight is an important risk factor in asthma .…”
Section: Introductionmentioning
confidence: 99%
“…The clinical course of inflammatory lung diseases is influenced by several factors including sex, hormones, and poor air quality (Doherty et al 2009;Liptzin et al 2015;Silva et al 2017). Sex differences in lung disease incidence, prevalence, and severity have been noted for years, as well as increased prevalence rates for asthma, chronic obstructive pulmonary disease (COPD), and other inflammatory diseases in women versus men (Fuseini and Newcomb 2017;Tsiligianni et al 2017;Center for Disease Control and Prevention, 2018;Shah and Newcomb 2018). The number of women diagnosed with asthma, bronchitis, emphysema, COPD, pneumonia, and lung cancer has significantly increased in the past decade at higher rates than for men, and the mortality associated with many of these conditions is also now higher for women than men (Martinez et al 2007;Aryal et al 2014;Jenkins et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…12 Ruchi Shah et al, proposed that in childhood asthma is more prevalent among males and in adulthood more prevalent in women and hormone fluctuations alter the symptoms of asthma among women. 13 Iris Koper et al, also agreed on gender differences of asthma. 14 Be´ne´dicte Leynaert et al, proposed that non allergic asthma is more frequent in women than men and female sex is an independent risk factor for nonallergic asthma.…”
Section: Discussionmentioning
confidence: 94%